White magic, black magic in the European Renaissance - Zambelli, Paola (Studies in medieval and Reformation traditions, 2007)
The ideas of philosophers (Ficino, Pico, Della Porta, Bruno) on magic interfered with popular alternative and witchcraft rites. This book focuses on "wandering scholastics" (Trithemius, Agrippa, Paracelsus, Bruno) and is suitable for those interested in Renaissance mentality.